Efficacy of rasagiline and selegiline in Parkinson’s disease: a head-to-head 3-year retrospective case–control study - Cereda, Emanuele (J Neurol, 2017)
Monoamine oxidase type B (MAO-B) inhibitors, such as selegiline and rasagiline, can be used as monotherapy or adjuvant therapy to levodopa in Parkinson’s disease (PD). Data on long-term efficacy of MAO-B inhibitors are limited with no head-to-head comparison available to date. The aim of this case–control retrospective study was to analyze data from patients with PD attending the Parkinson Institute (Milan, Italy) over a 6-year period (2009–2015) and compare the effects of selegiline and rasagiline on levodopa treatment outcomes. Patients with PD treated with either selegiline (n = 85) or rasagiline (n = 85) for 3 years as well as a control group of patients (N = 170) who have never received MAO-B inhibitors, were matched for gender, disease duration (±1 year) and age (±1 year) at baseline assessment (ratio 1:1:2). The Unified PD Rating Scale and the Hoehn–Yahr staging system were used for clinical comparisons. At baseline, mean PD duration was 6.5 years and clinical features were comparable across all three groups. After a mean follow-up of approximately 37 months, no differences in clinical progression of motor and non-motor symptoms were observed between the three groups. However, MAO-B inhibitor use was associated with ~2-fold lower change in daily dose of levodopa (p < 0.001) and lower dyskinesia scores (p = 0.028) than non-users. No intra-class differences were observed between selegiline and rasagiline. Long-term use of MAO-B inhibitors resulted in a significant reduction in levodopa requirements and a lower frequency of dyskinesias in patients with PD. Selegiline and rasagiline had equal efficacy in controlling motor symptoms in PD patients on optimized therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00415-017-8523-y) contains supplementary material, which is available to authorized users.